Strategi Pengembangan Istana Tambakbulusan Sebagai Destinasi Wisata Bahari di Kabupaten Demak - Fajar Setyo Rahmanto; Jasanta Peranginangin; Made Prasta Yostitia Pradipta (Sekolah Tinggi Pariwisata Sahid Surakarta, 2020)
This skripsi examines the strategies or steps taken by the management of Istana Tambakbulusan in developing Istana Tambakbulusan as a marine tourism destination in Demak Regency. Including the constraints faced in the development process. The writing of this skripsi uses descriptive qualitative research to examine the strategy for developing Istana Tambakbulusan as a marine tourism destination in Demak Regency. The method of data collection is in-depth interviews with managers, in addition, other data is carried out by observation and field data. The data obtained were then analyzed qualitatively by data triangulation method and presented descriptively. The results of this study found that the strategy of developing attractions in the marine tourism destination of Istana Tambakbulusan will revive old activities or events that are no longer implemented, namely